European Cities in Dynamic Competition : Theory and Case Studies on Urban Governance, Strategy, Cooperation and Competitiveness /: Theory and Case Studies on Urban Governance, Strategy, Cooperation and Competitiveness. ([2018]) - Unknown
No abstract available